2017
DOI: 10.3126/ajms.v8i6.18270
|View full text |Cite
|
Sign up to set email alerts
|

Typh fevers: a combination of Typhoid and Typhus

Abstract: Typhoid fever is caused by Salmonella typhi, while typhus fever is a rickettsial infection. In both cases the patients present with almost similar pattern of illness and are often misdiagnosed. This is the case of a young lady who presented with 10 days history of fever and was diagnosed to have typhoid fever. She continued to be febrile despite ceftriaxone therapy. She was later found to have a typhus coinfection and improved with addition of doxycycline.Asian Journal of Medical Sciences Vol.8(6) 2017 40-41

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…(P-value 0.001) During the past century before 1990, the numbers of typhoid fever patients were limited because of good standard of living, but during the 90th Period especially after the Second Gulf War Typhoid fever outbreak disease spread more than threefold between 1996-2000 because of poor sanitation and water supplies, , Poor nutrition and Deterioration of preventive health programmers as a result of economic sanction against the country [16] There were 29,000 cases in 2003 and 5460 in the first quarter of 2004 [17], also the process of disposing weapons of mass destruction, including biological weapons by United Nations inspection teams, may have played a major role in this outbreak of typhoid fever, especially after the Kurdistan Research Centres(Kurdish-British medical and scientific support group) confirmed the presence of typhoid bacteria, even using them in the first Gulf War [18]where Typhoid fever in aerosolized form can be a potential biological weapon, and sources reported that Iraq experimented with typhoid fever as a possible biological weapons agent. [20]. The presentation of both typhoid fever and rickettsial typhus, endemic or epidemic sometimes nearly similar that difficult to differentiate between both diseases so in case of co-infection of typhoid and typhus fever can be overlooked if not suspected clinically.…”
Section: Resultsmentioning
confidence: 99%
“…(P-value 0.001) During the past century before 1990, the numbers of typhoid fever patients were limited because of good standard of living, but during the 90th Period especially after the Second Gulf War Typhoid fever outbreak disease spread more than threefold between 1996-2000 because of poor sanitation and water supplies, , Poor nutrition and Deterioration of preventive health programmers as a result of economic sanction against the country [16] There were 29,000 cases in 2003 and 5460 in the first quarter of 2004 [17], also the process of disposing weapons of mass destruction, including biological weapons by United Nations inspection teams, may have played a major role in this outbreak of typhoid fever, especially after the Kurdistan Research Centres(Kurdish-British medical and scientific support group) confirmed the presence of typhoid bacteria, even using them in the first Gulf War [18]where Typhoid fever in aerosolized form can be a potential biological weapon, and sources reported that Iraq experimented with typhoid fever as a possible biological weapons agent. [20]. The presentation of both typhoid fever and rickettsial typhus, endemic or epidemic sometimes nearly similar that difficult to differentiate between both diseases so in case of co-infection of typhoid and typhus fever can be overlooked if not suspected clinically.…”
Section: Resultsmentioning
confidence: 99%
“…There are a few case reports on scrub typhus and enteric fever co-infection using Weil-Felix test and Widal, respectively. [21222324] Gupta et al . conducted a study in which 10 out of 258 serum samples of patients with acute febrile illness were positive for both scrub typhus and leptospirosis by IgM ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Epidemic typhus may be misdiagnosed as typhoid fever. 1,3 Rickettsia is emerging in this subcontinent as a cause of clinically nonspecific febrile illness. 4 Rickettsia prowazekii causes epidemic typhus in which the vector is body louse.…”
Section: Introductionmentioning
confidence: 99%